Laparoscopic Intragastric Surgery With Endoscopic Assistance: A 2 Gastrostomy Approach With Multiple Applications. Issue 5 (October 2017) - Gabriel, Emmanuel; Rosso, Kelly; Shahab, Danish; Shah, Rupen; Bain, Andrew; Kukar, Moshim; Hochwald, Steven N.
Abstract : Purpose: Laparoscopic intragastric resection is a surgical modality with acceptable oncologic outcomes for gastrointestinal stromal tumors and leiomyomas, particularly for masses located near the gastroesophageal junction (GEJ). We describe our technique of 2 gastrostomy laparoscopic, intragastric resection with endoscopic assistance. Methods: We detail our technique and report a unique application of this versatile approach. Results: Between December 2015 and July 2016, 4 patients underwent our combined technique of intragastric surgery. Complete resection was performed in the 2 patients who had gastrointestinal stromal tumors and 1 patient with a leiomyoma without complications. One patient had the unique diagnosis of gastritis cystica profunda. This mass could not be resected, but an effective Tru-cut core needle biopsy was obtained, and the mass was able to be diagnosed and decompressed. Conclusions: Our technique of 2 gastrostomy laparoscopic intragastric surgery is feasible and offers an effective oncologic approach for resection of tumors near the GEJ.